Effectiveness of planned teaching programme regarding worm infestation on knowledge among mothers of under-five children in rural area of Lucknow district - Yadav, Sandeep; Kumar, Rohitash; Singh, S. K. (International Journal Of Community Medicine And Public Health, 2020)
Background: According to the World Health Organization 241 million children between the ages of 1 and 14 years are at high risk of parasitic intestinal worms in India. As per the first-post news updated November 24, 2019, At least 241 million children below the age of 14 years are at high risk of getting stomach worms in India. The study was conducted with the objective to assess the level of knowledge and effectiveness of planned teaching programme on knowledge regarding worm infestation among the mothers of under-five children. Methods: The experimental pre-test-post-test control group design used and probability random sampling technique was adapted to select 92 mothers for both groups. Tool was used semi-structured knowledge questionnaire and planned teaching programme was implemented only on experimental group. Results: The results revealed that in experimental group post-test mean and SD score i.e. (16±3.56) was significantly higher the pre-test score i.e. (8.26±3.79) and compared the ‘t’ value, calculated ‘t’ value was (3.76) at the level of significance (0.05) and tabulated with 45 degree of freedom i.e. (2.01). So, it showed that the planned teaching programme regarding worm infestation among the mothers of under-five children in rural area was found effective. Conclusions: The present study assessed the knowledge among mothers of under-five children regarding worm infestation and found that mothers had poor knowledge related to worm infestation. After the planned teaching programme on worm infestation there was significant improvement on knowledge of the mothers of under-five children regarding worm infestation in experimental group.